p53 Family: Role of Protein Isoforms in Human Cancer - Wei, Jinxiong; Zaika, Elena; Zaika, Alexander (Journal of Nucleic Acids, 2012)
TP53, TP63, and TP73 genes comprise the p53 family. Each gene produces protein isoforms through multiple mechanisms including extensive alternative mRNA splicing. Accumulating evidence shows that these isoforms play a critical role in the regulation of many biological processes in normal cells. Their abnormal expression contributes to tumorigenesis and has a profound effect on tumor response to curative therapy. This paper is an overview of isoform diversity in the p53 family and its role in cancer.